3D aerodynamic admittances of streamlined box bridge decks. (15th January 2019) - Ma, Cunming; Wang, Junxin; Li, Q.S.; Liao, Haili
Highlights: The fluctuating pressures of bridge decks were measured with different turbulence. The coherences of the buffeting force of the box bridge decks were investigated. An Empirical formula for the 3D aerodynamic admittance was proposed. An Empirical formula for the coherence of buffeting forces was proposed. Abstract: Via wind tunnel tests, the fluctuating pressures on the surfaces of three streamlined box bridge models are measured in two turbulent flow-fields with different turbulence characteristic parameters. The distributions of the fluctuating pressures on the models are presented and discussed in detail. The correlations between the fluctuating pressures on a crosswise section and the coherences of the buffeting force along the spanwise direction of the models are investigated. Furthermore, the 3D aerodynamic admittances of the models are identified and analyzed. An empirical formula for determining the 3D aerodynamic admittance of a streamlined bridge deck is proposed based on the extensive results of the experimental data and analysis. Clarifications are made regarding the differences between the real 3D aerodynamic admittances and the existing formulas. It is then further revealed that the real value of a 3D aerodynamic admittance is not between 1 and the number determined by the Sears function. This is followed by a rational explanation for the observations based on the experimental results.